'What's happening?' A content analysis of concussion-related traffic on Twitter. Issue 4 (15th March 2011) - Sullivan, S John; Schneiders, Anthony G; Cheang, Choon-Wi; Kitto, Emma; Lee, Hopin; Redhead, Jason; Ward, Sarah; Ahmed, Osman H; McCrory, Paul R
Abstract : Background: Twitter is a rapidly growing social networking site (SNS) with approximately 124 million users worldwide. Twitter allows users to post brief messages ('tweets') online, on a range of everyday topics including those dealing with health and wellbeing. Currently, little is known about how tweets are used to convey information relating to specific injuries, such as concussion, that commonly occur in youth sports. Objective: The purpose of this study was to analyse the online content of concussion-related tweets on the SNS Twitter, to determine the concept and context of mild traumatic brain injury as it relates to an online population. Study design: A prospective observational study using content analysis. Methods: Twitter traffic was investigated over a 7-day period in July 2010, using eight concussion-related search terms. From the 3488 tweets identified, 1000 were randomly selected and independently analysed using a customised coding scheme to determine major content themes. Results: The most frequent theme was 'news' (33%) followed by 'sharing personal information/situation' (27%) and 'inferred management' (13%). Demographic data were available for 60% of the sample, with the majority of tweets (82%) originating from the USA, followed by Asia (5%) and the UK (4.5%). Conclusion: This study highlights the capacity of Twitter to serve as a powerful broadcast medium for sports concussion information and education.